TINJAUAN PUSTAKA: DAMPAK TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA DI ERA DIGITAL - Pamungkas, Ibrahim Bali; Praditya, Alvin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study examines the effects of Information and Communication Technology (ICT) on employee performance measurement and appraisal, focusing on how ICT can improve the accuracy and fairness of evaluations. The research methodology employed is a comprehensive literature review. Relevant articles published in Indonesian from 2019 to 2023 were retrieved from the GARUDA database. Keywords and phrases related to ICT and performance were used to search for abstracts or full-text journal articles. These were then reviewed and analyzed according to specific criteria. The results of the review of 15 journals over the past 5 years highlight 7 key points: 1) Enhanced Performance Monitoring through Real-Time Data, 2) Integration of Performance Management Systems with HR Functions, 3) Use of Artificial Intelligence for Personalized Feedback, 4) Streamlining of Evaluation Processes through Automation, 5) Adoption of Standardized Performance Metrics, 6) Employee Engagement through Interactive Feedback Mechanisms, 7) Secure Data Storage and Confidentiality.